2003
DOI: 10.1083/jcb.200308071
|View full text |Cite
|
Sign up to set email alerts
|

Yeast homotypic vacuole fusion requires the Ccz1–Mon1 complex during the tethering/docking stage

Abstract: The function of the yeast lysosome/vacuole is critically linked with the morphology of the organelle. Accordingly, highly regulated processes control vacuolar fission and fusion events. Analysis of homotypic vacuole fusion demonstrated that vacuoles from strains defective in the CCZ1 and MON1 genes could not fuse. Morphological evidence suggested that these mutant vacuoles could not proceed to the tethering/docking stage. Ccz1 and Mon1 form a stable protein complex that binds the vacuole membrane. In the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 24 publications
7
103
0
2
Order By: Relevance
“…Surprisingly, Mon1a, unlike Mon1b, does not play a role in EE docking. This is, however, consistent with previous finding that Mon1b, but not Mon1a, is a core component of the class C VPS/ HOPS complex [36], which is required for EE homotypic docking and fusion.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Surprisingly, Mon1a, unlike Mon1b, does not play a role in EE docking. This is, however, consistent with previous finding that Mon1b, but not Mon1a, is a core component of the class C VPS/ HOPS complex [36], which is required for EE homotypic docking and fusion.…”
Section: Discussionsupporting
confidence: 81%
“…Here, we show that the 11-aa insertion in the PTB domain also determines the role of Numb in the control of endocytic trafficking. We show although all isoforms of Numb and Numblike can bind to Mon1a and Mon1b [36,47], only Numb 65, Numb 71 and partially Numblike are responsible for EE docking during homotypic fusion. In line with this finding, we observed that Numb 65, Numb 71 and partially Numblike localize on EEs in the perinuclear region, where endocytic sorting occurs in the mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations